Antimycobacterial potency and cytotoxicity study of three medicinal plants - Patrick Valere Tsouh Fokou; Regina Appiah- Opong; Dorothy Yeboah-Manu; Abena Adomah Kissi-Twum; Lauve Rachel Tchokouaha Yamthe; Aristide Laurel Mokale Kognou; Phyllis Addo; Fabrice Fekam Boyom; Alexander Kwadwo Nyarko (International Journal of Mycobacteriology, 2016)
Objective/Background: Mycobacterial infections including tuberculosis, leprosy, and buruli ulcer are among the most prevalent, debilitating, and deadly tropical diseases, especially in Sub-Saharan Africa. The development of drug resistance to the currently available drugs and the poor compliance emphasize the need for new chemotherapeutic agents. This study was designed to evaluate the in vitro activity of Cleistopholis patens, Annona reticulata, and Greenwayodendron suaveolens against Mycobacterium smegmatis. The safety on normal liver cells was also assessed. Methods: The crude extracts, fractions, and subfractions were tested against M. smegmatis and for cell cytotoxicity on WRL-68, normal human hepatocyte using microdilution resazurin-based assays. The phytochemical screening was performed using standard methods. Results: Most of the extracts, fractions, and subfractions inhibited the growth of M. smegmatis with minimum inhibitory concentration (MIC) values ranging from 6.25 μg/mL to 125 μg/mL. The subfractions P12 and P29 from G. suaveolens twig were more potent with MIC values of 6.25 μg/mL and 25 μg/mL, respectively. Fruit crude extract and root CH2Cl2 fraction from A. reticulata also showed activity with MIC values of 50 μg/mL and 25 μg/mL, respectively. Crude extracts from the twig and stem bark of C. patens displayed inhibition at MIC values of 125 μg/mL and 100 μg/mL, respectively. Majority of active extracts showed no cell cytotoxicity, except the extract from C. patens with IC50 ranging from 41.40 μg/mL to 93.78 μg/mL. The chemical investigation of the promising extracts revealed the presence of phenols, alkaloids, glycosides, triterpenes, and acetogenins. Conclusion: The results achieved from this preliminary antimycobacterial drug discovery study supported the traditional claims of C. patens, A. reticulata, and G. suaveolens in the treatment of mycobacterial infections. Meanwhile, further fractionation is required to characterize the active ingredients.